Ethical and practical challenges in implementing informed consent in HIV/AIDS clinical trials in developing or resource-limited countries - Kyriaki Mystakidou; Irene Panagiotou; Stelios Katsaragakis; Eleni Tsilika; Efi Parpa (SAHARA-J, 2009)
Background/rationale: Ethical issues regarding HIV/AIDS human research in the developing world remain under continuous evaluation; a critical area of concern includes informed consent. This paper reviews several of the most important ethical and practical aspects of informed consent in HIV research in developing countries. Enhancement of overall understanding of such key issues might promote higher ethical standards of future research. Objectives: The major objective was to address informed consent in human research in non-Western societies, and specifically in HIV clinical trials of affected adults. Secondary end-points included the consent complexities in HIV research involving vulnerable patient populations in resource-limited nations, such as children, adolescents and women. Methods: A systematic review of the published literature using MEDLINE and EMBASE from 1998 until December 2008 was performed, using the search terms ‘HIV/AIDS’, ‘informed consent’, ‘clinical trials’, ‘developing world’. Results: Ethical complexities such as participants' diminished autonomy, coercion or monetary inducement, language difficulties, illiteracy or lack of true understanding of the entire study, cultural barriers mainly due to communitarianism and social diversities were identified in the 44 studies reviewed. Informed consent of vulnerable patient populations must be tailored to their sex and developmental age, while counselling is fundamental. Children and adolescents' assent must be ensured. Local language is to be used, while trusted community leaders and local cultural representatives may convey information. Discussion: Despite the heterogeneity of studies, similarities were identified. Providing adequate and comprehensive information and assessing the true understanding of the research represent fundamental prerequisites. Potential solutions to the critical areas of concern include peer counselling and meetings with local community leaders or local cultural representatives. Conclusions: International investigators of HIV human research should bear in mind these ethical issues and their potential solutions, when trying to ensure ethical research conduct, based on a truly informed and culturally relevant consent.